High-grade B-cell lymphoma masquerading as peritoneal lymphomatosis. Issue 8 (13th August 2019) - Kareff, Samuel; Yin, Chao; Feigert, John
Abstract : Peritoneal lymphomatosis represents a rare presentation of any type of non-Hodgkin's lymphoma, with relatively few cases reported in the literature. We present here the case of a 61-year-old man who originally presented with increased abdominal distention associated with shortness of breath and diaphoresis who was found to have evidence of peritoneal carcinomatosis on CT scan. Biopsy confirmed diffuse large B-cell lymphoma, and the working diagnosis was subsequently modified to peritoneal lymphomatosis. The patient was treated with dose-adjusted etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin and rituximab (DA-EPOCH-R) therapy with initially good response. His course was complicated by tumour lysis syndrome. We review the limited literature discussing peritoneal lymphomatosis and discuss the importance of facilitating rapid and efficacious treatment.